2001
DOI: 10.1200/jco.2001.19.15.3506
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dense Doxorubicin, Docetaxel, and Granulocyte Colony-Stimulating Factor Support With or Without Tamoxifen as Preoperative Therapy in Patients With Operable Carcinoma of the Breast: A Randomized, Controlled, Open Phase IIb Study

Abstract: A dose-dense regimen of ADoc with G-CSF offers high compliance, moderate toxicity, and rapid efficacy as a form of preoperative chemotherapy in operable breast cancer. Concurrent treatment with tamoxifen for 8 weeks could not improve the pathologic response rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
1
11

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 141 publications
(77 citation statements)
references
References 14 publications
4
61
1
11
Order By: Relevance
“…Since availability of HER2 status is a mere function of time and not associated with prognostically important patient or tumor characteristics (Table 2), this restriction is unlikely to have introduced bias. Other unmeasured confounders might be tumor characteristics associated with time, however median tumor size and nodal status in the early Gepardo trial [9] was similar to the most recent GeparQuattro [14] trial.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Since availability of HER2 status is a mere function of time and not associated with prognostically important patient or tumor characteristics (Table 2), this restriction is unlikely to have introduced bias. Other unmeasured confounders might be tumor characteristics associated with time, however median tumor size and nodal status in the early Gepardo trial [9] was similar to the most recent GeparQuattro [14] trial.…”
Section: Discussionmentioning
confidence: 72%
“…Between 1998 and 2006, a total of eight major prospective neoadjuvant trials in 6625 breast cancer patients were conducted in Germany [9,10,11,12,13,14,15,16,17,18]. Details of design and conduct of individual trial were previously reported (Table 1).…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Between 1998 and 2010, 9,197 breast cancer patients were enrolled in nine prospectively randomized multicentre, neoadjuvant trials in Germany, all having comparable main eligibility criteria [9,11,12].…”
Section: Methodsmentioning
confidence: 99%